Determinants of Micro Enterprise Owners' Loyalty towards Their Favourite Banks. (15th June 2016) - Kasuma, Jati; Ung, Ting Su; Kanyan, Agnes; Kamri, Thalany; Yacob, Yusman
Abstract: Banking is a service that lies in a very competitive industry in most developed and developing countries, with different brands competing in a scenario of increasing banking and credit penetration. In a business-to-professional setting for banking, the range of services that a client uses with a bank is very high compared to retail banking. Thus, this paper would like to examine the loyalty of the micro-enterprise owners towards their favourite banks. Using both local and international banks in Malaysia as the focus of the study, an exploratory research was carried out to assess micro-enterprise owners' level of loyalty to their banks. Self-administered questionnaires were collected from 356 banks' business customers of various conventional and Islamic banks. The findings from this research have shown that a bank's reputation, quality services as well as customer relationship have a direct relationship to micro-enterprise owners' loyalty. The micro-enterprise owners believed that as long as the bank provides good services, a good income is being generated through them with the security factor taken into consideration. This study's findings could provide important directions for the development of a holistic framework to explain the formation and structure of micro-enterprise owners' loyalty towards banking and financial services industries.